Cryoablation and immune synergistic effect for lung cancer: A review - Tian, Yulong; Qi, Xingshun; Jiang, Xin; Shang, Liqi; Xu, Ke; Shao, Haibo (Frontiers in Immunology, 2022)
Abstract: The preferred treatment for lung cancer is surgical resection, but a large number of patients are not suitable for surgical resection in clinic. CT-guided cryoablation and immunotherapy can play an important role in patients with advanced lung cancer who are ineligible for surgery. CT-guided cryoablation has been widely used in the clinical treatment of lung tumors due to its advantages of less trauma, fewer complications, significant efficacy and rapid recovery. Cryoablation can not only cause tumor necrosis and apoptosis, but also promote the release of tumor-derived autoantigens into the blood circulation, and stimulate the host immune system to produce a good anti-tumor immune effect against primary and metastatic tumors. Since the study of immune checkpoint inhibitors has proved that lung cancer can be an immunotherapeutic response disease, the relationship between cryoablation and immunotherapy of lung cancer has been paid more attention. Therefore, we reviewed the literature on cryoablation for lung cancer, as well as the research progress of cryoablation combined with immunotherapy.